Evaluation of the safety and immunogenicity of the oral inactivated multivalent enterotoxigenic Escherichia coli vaccine ETVAX in Bangladeshi adults in a double-blind, randomized, placebo-controlled Phase I trial using electrochemiluminescence and ELISA assays for immunogenicity analyses. Issue 37 (3rd September 2019) - Akhtar, Marjahan; Chowdhury, Mohiul I.; Bhuiyan, Taufiqur R.; Kaim, Joanna; Ahmed, Tasnuva; Rafique, Tanzeem A.; Khan, Arifuzzaman; Rahman, Sadia I.A.; Khanam, Farhana; Begum, Yasmin A.; Sharif, Mir Z.; Islam, Laila N.; et al.
Highlights: The killed oral ETEC vaccine ETVAX ± dmLT adjuvant was safe in Bangladeshi adults. All vaccinees responded to all 5 primary vaccine antigens in ALS specimens. A majority of vaccinees responded to ≥4 antigens in plasma specimens. A sensitive electrochemiluminescence assay was established for small sample volumes. ALS responses measured by electrochemiluminescence and ELISA assays correlated well. Abstract: The safety and immunogenicity of the second generation oral enterotoxigenic Escherichia coli (ETEC) vaccine ETVAX, consisting of inactivated recombinant E. coli strains over-expressing the colonization factors (CFs) CFA/I, CS3, CS5 and CS6 and the heat labile toxoid LCTB A, were evaluated in Bangladeshi volunteers. To enable analysis of antibody responses against multiple vaccine antigens for subsequent use in small sample volumes from children, a sensitive electrochemiluminescence (ECL) assay for analysis of intestine-derived antibody-secreting cell responses using the antibodies in lymphocyte secretions (ALS) assay was established using Meso Scale Discovery technology. Three groups of Bangladeshi adults (n = 15 per group) received two oral doses of ETVAX with or without double mutant LT (dmLT) adjuvant or placebo in the initial part of a randomized, double-blind, placebo-controlled, age-descending, dose-escalation trial. CF- and LTB-specific ALS and plasma IgA responses were analyzed by ECL and/or ELISA. ETVAX was safe and well tolerated in the adults. Magnitudes of IgA ALS responses determined by ECL and ELISA correlated well (r = 0.85 to 0.98 for the five primary antigens, P < 0.001) and ECL was selected as the ALS readout method. ALS IgA responses against each of the primary antigens were detected in 87–100% of vaccinees after the first and in 100% after the second vaccine dose. Plasma IgA responses against different CFs and LTB were observed in 62–93% and 100% of vaccinees, respectively. No statistically significant adjuvant effect of dmLT on antibody responses to any antigen was detected, but the overall antigenic breadth of the plasma IgA response tended to favor the adjuvanted vaccine when responses to 4 or more or 5 vaccine antigens were considered. Responses in placebo recipients were infrequent and mainly detected against single antigens. The promising results in adults supported testing ETVAX in descending age groups of children. ClinicalTrials.gov Identifier:NCT02531802 .